Evaluación de dosis de silicio en el rendimiento del pepino hibrido (cucumis sativus l) variedad stonewall f1, Lamas – San Martin - Pinedo Garcia, Juan Angel (2011)
This paper titled "Evaluation of silicon doses on the performance of hybrid cucumber (Cucumis sativus L) variety STONEWALL F1, Lamas - San Martin" aimed to determine the optimal dose of silicon foliar application in hybrid cucumber variety STONEWALL F1 and perform economic analysis of the treatments under study, for which we evaluated 4 treatments: T0 (no application), T1 (1.2 l/ha), T2 (1.8 l/ha) and T3 (2.4 l/ha). The parameters evaluated were: percentage of emergence, plant height, number of fruits produced per plant, number of fruit set per plant, fruit length, fruit diameter, fruit weight, yield t/ha, and finally conducted an economic analysis of all treatments studied. The major findings were: T3 treatment (2.4 Liters of Silicon x ha-1), was the one who threw the biggest and best average values of productivity indicators being these of 64.96 fruits per plant, fruit set per plant 12.82, 10.47 fruit diameter cm, 26.10 cm fruit length and weight of 575.67 g per fruit harvested respectively T0 treatment (without silicon application), was the one who threw the lowest average values, being able to determine that as reduced dose of silicon in cucumber plants also decreased the average values of productivity indicators and treatment they received higher performance (249.45 t/ha), net income (S/.9 361.40) and the highest percentage in return (60.07%) was the T3, then T2, T1 and T0 yields of tn.ha-1 220.39, 167.07 and 119.01 t/ha respectively and hence lower values of net income and percentage of profitability.